From Head to Foot (2011)
Simon Saldarriaga, participant of Meeting Questions 2011: "The University of children has opened my mind a lot – now my curiosity is broader – has taught me many things, and has given me a lot of knowledge. My favorite question was how planes fly I really like science, and physics intrigues me, plus I love to travel and every time I go on a plane I'm impressed that I can fly despite being so heavy."